Effect of Continuous Cropping Generations on Each Component Biomass of Poplar Seedlings during Different Growth Periods - Jiangbao Xia; Shuyong Zhang; Tian Li; Xia Liu; Ronghua Zhang; Guangcan Zhang (The Scientific World Journal)
In order to investigate the change rules and response characteristics of growth status on each component of poplar seedling followed by continuous cropping generations and growth period, we clear the biomass distribution pattern of poplar seedling, adapt continuous cropping, and provide theoretical foundation and technical reference on cultivation management of poplar seedling, the first generation, second generation, and third generation continuous cropping poplar seedlings were taken as study objects, and the whole poplar seedling was harvested to measure and analyze the change of each component biomass on different growth period poplar leaves, newly emerging branches, trunks and root system, and so forth. The results showed that the whole biomass of poplar seedling decreased significantly with the leaf area and its ratio increased, and the growth was inhibited obviously. The biomass aboveground was more than that underground. The ratios of leaf biomass and newly emerging branches biomass of first continuous cropping poplar seedling were relatively high. With the continuous cropping generations and growth cycle increasing, poplar seedling had a growth strategy to improve the ratio of root-shoot and root-leaf to adapt the limited soil nutrient of continuous cropping.